Mutualism between honeyguides, beekeepers and honey-hunters in southern Tanzania - Kilawi, Amana (Department of Biological Sciences, 2024)
The greater honeyguide (hereafter “honeyguide”) is a wax-eating bird species that engages in a remarkable mutualism with humans. Honeyguides use a specialised chattering call to guide honeyhunters to bees' nests, which honey-hunters harvest with the help of smoke and tools. Honey-hunters increase their harvesting yield by finding bees' nests with the help of honeyguides, and honeyguides feed on leftover beeswax. The relationship between honeyguides and honey-hunters in search of wild bees' nests has been well studied, but we know little about the relationship between honeyguides and beekeepers who harvest honey from man-made beehives. I studied the relationship between people and honeyguides in southern Tanzania, in and/or around Ruaha National Park, Rungwa Game Reserve, and Katavi National Park. I visited 20 villages and interviewed 150 people who either practice beekeeping or honey-hunting or do both. I also visited beekeeping camps to observe how people harvest and process honey, and I set camera traps to investigate the fate of beeswax left behind. Specifically, I asked: (i) what is the relationship between honeyguides and beekeepers? (ii) Does honey-hunting with honeyguides persist in southern Tanzania despite beekeeping and if so, how does it function? (iii) What are the ecosystem effects of honey harvesting in southern Tanzania? (iv) What is the future of human-honeyguide interactions in southern Tanzania? Overall, my results suggest that (i) surprisingly, the relationship between honeyguides and beekeepers is often a mutualism, because beekeepers use honeyguides to find beehives that are ready to harvest, and reward honeyguides with an empty wax comb. (ii) Despite being illegal, honey-hunting with honeyguides persists in southern Tanzania; all 66 honey-hunters mentioned that they use honeyguides to find bees ‘nests, and the majority use a specialised calls (particularly “prrrr-prrrr mama”) to communicate with honeyguides. (iii) Honey-hunters typically cut down trees to harvest wild beehives, but beekeepers also destroy trees by cutting down or debarking them to make different types of traditional beehives, typically cylinders made of either bark or solid wood. Many beekeepers possess hundreds of hives, suggesting that beekeeping is not less destructive to trees than honey-hunting, and may be more so. (iv) Interview responses suggested that people are losing interest in following honeyguides due to beekeeping replacing honey-hunting, and due to people, who still want to honey-hunt being constrained from doing so by protected areas, and possibly by climate change and habitat loss causing bee declines. Conversely, interview responses also highlighted beekeepers' use of honeyguides to find their own beehives as a reason why human-honeyguide mutualism continues to thrive in southern Tanzania.